The Effectiveness of Anti-Bullying Teaching Material Through a Deep Learning Approach Based on Project-Based Learning - Kristiwi Estuningsih; Harmanto; Septina Alrianingrum (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2025)
Bullying remains one of the most serious challenges in Indonesian education, with far-reaching impacts on students' psychological, social, and academic development. Bullying that occurs in schools not only reduces learning motivation but also hinders character formation and the development of human values ​​​​in line with Pancasila. This study aims to describe the effectiveness of